EFEKTIVITAS SENAM HAMIL DALAM MENURUNKAN NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER I DAN TRIMESTER III - Wardani, Ika Kania Fatdo; Nahria, Syarifatun; Rahayu, Sri (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2025)
Background: Low back pain is a complaint that is often experienced by pregnant women, especially in the first trimester due to hormonal adaptation and in the third trimester due to increased mechanical load on the body. This condition can interfere with daily activities, quality of life, and decrease comfort during pregnancy. Pregnancy exercises are one of the non-pharmacological interventions that are believed to help reduce back pain complaints through stretching exercises and muscle relaxation. Objective: To determine the effectiveness of pregnancy exercises in reducing the intensity of low back pain in pregnant women in the first trimester and third trimester. Methods: This study used a quasi experiment design with a pretest-posttest one group design approach. The sample consisted of pregnant women in the first trimester and third trimester who experienced low back pain (30 people), selected by total sampling technique. Interventions in the form of pregnancy exercises were carried out regularly according to standards during several meetings. Back pain intensity was measured using the Verbal Descriptor Scale (VDS) before and after the intervention. Data analysis used the Wilcoxon statistical test (0.000) to look at the effects before and after treatment. Results: The results showed a significant decrease in the intensity of low back pain after pregnancy exercises, both in pregnant women in the first trimester and third trimester (p < 0.05). Conclusion: Pregnancy exercises have been shown to be effective in reducing low back pain in pregnant women in the first trimester and third trimester. This intervention may be recommended as part of obstetric care to improve maternal comfort during pregnancy.